66‐2: Printed Carbon Nanotube Thin‐film Transistors and Application in OLED Backplane Circuits. Issue 1 (May 2017) - Xu, Wenya; Xu, Qiqi; Zhou, Chunshan; Gu, Weibing; Lin, Jian; Zhao, Jianwen; Cui, Zheng
Abstract : In this work, we reported a valid method to sort large‐diameter semiconducting single‐walled carbon nanotubes (sc‐SWCNTs) from commercial arc discharge SWCNTs by different conjugated organic compounds. Seven kinds of high‐purity sc SWCNT inks were achieved. As‐prepared sc‐SWCNT inks were directly used to fabricate printed SWCNT TFT arrays and backplane circuits on rigid substrates. It was found that printed SWCNT TFT devices exhibited high‐performance with low operating voltage (±2 V), small subthreshold swing (ss), small hysteresis, high mobility (more than 20 cm 2 /Vs) and high on/off ratios (up to 10 6 ). Printed 2T‐1C driving circuit exhibited high on/off ratio up to 10 5 and high output current up to 8×10 ‐5 μ A at Vdata, Vscan and Vdd of ‐2 V, respectively. Furthermore, 15×15 OLED pixel arrays were switched on with printed SWCNT driving circuits on glass substrates, suggesting printed SWCNT driving circuits have the potential as backplanes for active matrix OLED applications.